CORRELATION OF RELIGIOUS AND CULTURAL LITERACY BUILDING RELIGIOUS MODERATION IN ISLAMIC EDUCATION - Zidni Ilma Nafia; Dwi Hastuti (Edusoshum : Journal of Islamic Education and Social Humanities, 2023)
This research is motivated by the urgent need to understand the correlation between religious and cultural literacy in shaping religious moderation in the context of Islamic education. The purpose of this study is to identify and analyze the correlation between religious and cultural literacy in the context of Islamic education and see its impact on the formation of religious moderation. The research method used is qualitative with a review of literature studies. Data were collected and analyzed to identify patterns and relationships between religious literacy, cultural literacy, and religious moderation. The results showed a strong relationship between a good understanding of religion and the integration of cultural values in the formation of religious moderation. Islamic education that focuses on religious and cultural literacy can be an effective solution to face the challenges of extremism and intolerance. This research makes a significant contribution by providing a more in-depth look at how religious and cultural literacy can play a role in creating moderate Islamic education. The implications of these findings can be used as a basis for designing an Islamic education curriculum that is more effective and relevant to the demands of the times, producing Muslim individuals who are not only religiously competent but also have a moderate and tolerant attitude in facing the dynamics of global society